Advances in Ascochyta Research - Weidong Chen (Frontiers Research Topics, 2018)
Legume crops provide an excellent source of high quality plant protein and have a key role in arable crop rotations reducing the need for fertilizer application and acting as break-crops. However, these crops are affected by a number of foliar and root diseases, being ascochyta blights the most important group of diseases worldwide. Ascochyta blights are incited by different pathogens in the various legumes. A number of control strategies have been developed including resistance breeding, cultural practices and chemical control. However, only marginal successes have been achieved in most instances, most control methods being uneconomical, hard to achieve or resulting in incomplete protection. This eBook covers recent advances in co-operative research on these diseases, from agronomy to breeding, covering traditional and modern genomic methodologies.